2016
DOI: 10.21608/jhiph.2016.20201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa Oleifera on Lipid Profile in Rats

Abstract: Background: Coronary heart disease, stroke, atherosclerosis and hyperlipidemia are primary causes of death worldwide. Moringa Oleifera tree was used as a health supplement introduced to Africa from India. Its leaves have various biological activities, including hypolipidemic effect. Objective(s):The aim of present study was to assess the effect of Moringa Oleifera consumption on lipid profile and histopathology of the liver in hyperlipidemic rats. Methods: A total of 50 male albino rats were divided into five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
(19 reference statements)
2
3
0
3
Order By: Relevance
“…The increased expression of SNAP-23 could be attributed to the activity of the gene in stimulating the release of adiponectins and leptin from the adipocytes. This is in agreement with the investigated evidence by Samar et al [8], who reported that Moringa oleifera reduced total cholesterol, triglyceride, low density cholesterol, high density cholesterol and very low density cholesterol in rats and that it is more effective in prevention of hyperlipidemia. We also found no significant difference in the expression of SNAP25, Kv1.2, and GLP-1R genes among all the rats.…”
Section: Discussionsupporting
confidence: 93%
“…The increased expression of SNAP-23 could be attributed to the activity of the gene in stimulating the release of adiponectins and leptin from the adipocytes. This is in agreement with the investigated evidence by Samar et al [8], who reported that Moringa oleifera reduced total cholesterol, triglyceride, low density cholesterol, high density cholesterol and very low density cholesterol in rats and that it is more effective in prevention of hyperlipidemia. We also found no significant difference in the expression of SNAP25, Kv1.2, and GLP-1R genes among all the rats.…”
Section: Discussionsupporting
confidence: 93%
“…Rats orally preventable administered with aqueous extracts of the mixture of moringa and green tea reflected the highest significant decrease in TC and TG compared to control positive groups which were 98.78±0.12, 90.55±0. These results confirmed by the findings of Aborhyem et al, (2016) who compared Moringa oleifera with atorvastatin as a hypolipidemic drug in improving the lipid profile of mice fed an atherosclerotic diet; concluding that Moringa oleifera caused effective prevention of hyperlipidemia when compared to hypolipidemic drugs. Moreover, Bakr and Header (2014) studied the effect of aqueous green tea extract on obese mice and side effects on their liver condition, which led to a significant decrease in total cholesterol and lipid levels in the green tea-treated groups.…”
Section: Biochemical Serum Analysissupporting
confidence: 78%
“…In the present study, several histopathological changes were seen in the liver of HFD-fed animals either for 4 or 8 weeks; the hepatocytes undergo hydropic degeneration and become swollen and vacuolated, described as ballooning degeneration. The previous studies reported that the consumption of HFD may play crucial role in the pathogenesis of fatty liver resulting in hepatocellular damage and exaggerated hepatic steatosis that is associated with other factors such as oxidant stress, mitochondrial injury, fatty acids lipotoxicity, and inflammatory cytokines [19,20]. Tveden-Nyborg et al [21] attributed these changes to the oxidative stress of dyslipidemia that disturbed redox balance resulting in the damage of polyunsaturated lipids in the mitochondrial membrane associated with a reduced export of TG and a subsequent accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%